2017
DOI: 10.1038/s41598-017-02325-8
|View full text |Cite
|
Sign up to set email alerts
|

A Four-Biomarker Blood Signature Discriminates Systemic Inflammation Due to Viral Infection Versus Other Etiologies

Abstract: The innate immune system of humans and other mammals responds to pathogen-associated molecular patterns (PAMPs) that are conserved across broad classes of infectious agents such as bacteria and viruses. We hypothesized that a blood-based transcriptional signature could be discovered indicating a host systemic response to viral infection. Previous work identified host transcriptional signatures to individual viruses including influenza, respiratory syncytial virus and dengue, but the generality of these signatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 118 publications
3
54
0
5
Order By: Relevance
“…In a recent study by Herberg et al, a 2-transcript RNA signature [ FAM89A and IFI44L ) showed promising results in its ability to distinguish between bacterial and viral infections, demonstrating that the expression of IFI44L was increased in patients with viral infection, whereas expression of FAM89A was increased in patients with bacterial infection ( 118 ). Another recent study identified a four-gene expression signature in whole blood to distinguish viral infections from other etiologies ( 129 ). Human myxovirus resistance protein 1 (MxA) is an important intermediate product in the IFN-mediated antiviral response against a variety of viruses.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by Herberg et al, a 2-transcript RNA signature [ FAM89A and IFI44L ) showed promising results in its ability to distinguish between bacterial and viral infections, demonstrating that the expression of IFI44L was increased in patients with viral infection, whereas expression of FAM89A was increased in patients with bacterial infection ( 118 ). Another recent study identified a four-gene expression signature in whole blood to distinguish viral infections from other etiologies ( 129 ). Human myxovirus resistance protein 1 (MxA) is an important intermediate product in the IFN-mediated antiviral response against a variety of viruses.…”
Section: Introductionmentioning
confidence: 99%
“…This group of proteins includes ISG15 that has a diubiquitin-like structure (2). Isg15 is one of the genes most strongly upregulated in response to viral infection in a diversity of species, including humans (3,4). ISG15 is also induced by bacterial infections (5,6).…”
mentioning
confidence: 99%
“…Interestingly study failed to identify an immune response specific to bacterial pneumonia (Parnell et al, 2012). A study by Sampson et al (2017) which revealed different gene expression depending on virus or bacterial etiology, produced similar results. Should these abilities of a specific group of genes be confirmed, there is a real possibility of their implementation in clinical practice, which would affect antibiotic consumption, resistance development, etc.…”
Section: )mentioning
confidence: 87%